2019
DOI: 10.1017/s1041610219000073
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between childhood maltreatment and geriatric depression: the mediator effect of personality traits

Abstract: Background:Childhood maltreatment is an important factor associated with adverse mental health outcomes including geriatric depression and the “big five” personality characteristics. The objective of this study was to evaluate a model where personality characteristics mediate the relationship between childhood maltreatment and geriatric depression.Method:In this cross-sectional study, elderly subjects from socioeconomically disadvantaged neighborhoods of Porto Alegre, Brazil (n = 260) completed the Childhood T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
3
15
1
1
Order By: Relevance
“…Our findings suggest that low self-esteem is an important factor in geriatric depression especially in individuals with a previous history of physical abuse. In contrast to previously published studies [1,5,6], we found no significant correlation with personality traits, while our work focused specifically on TRD in the geriatric population. Our study sample was selected from highly specialised care centres in contrast to other published studies which focused on samples identified in the general population [1,5,6].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our findings suggest that low self-esteem is an important factor in geriatric depression especially in individuals with a previous history of physical abuse. In contrast to previously published studies [1,5,6], we found no significant correlation with personality traits, while our work focused specifically on TRD in the geriatric population. Our study sample was selected from highly specialised care centres in contrast to other published studies which focused on samples identified in the general population [1,5,6].…”
Section: Discussioncontrasting
confidence: 99%
“…We selected all cohort patients over 60 years of age for this study. Although the cutoff between geriatric and non-geriatric depression remains unclear, ranging from 60 [1,6,18,19] to 65 years old [20,21], we chose the age of 60 in order to compare our findings with those of most studies focusing on the impact of CM in depressive disorders [1,6,18,19]. Before participating in the full assessment, patients were interviewed by a psychiatrist at the expert centre in order to:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations